Climate Change, Quality of Government, and Migration - Federico Revelli; Tsung-Sheng Tsai (CESifo GmbH, 2024)
We study the impact of climate change on migration by developing a real options model that rigorously formalizes the trade-off between migrating early and procrastinating to learn more about the government's implementation of an adaptation policy that can effectively moderate the consequences of climate change. The model delivers an unambiguous guide to estimation of the impact of climate change on the occurrence of natural disasters and of the latter on migration decisions within a structural empirical model where the distinct mediation roles of the option value of waiting components (migration cost, home income, quality of government) are specified in a principled way. Evidence from panel data on international bilateral migration flows supports the main predictions of the theory and points to the key mediating role of government.
Keywords: C33; H31; O15; Q54; 330; option value of waiting; climate change adaptation; international migration